Boosting the peroxidase-like activity of gold nanoclusters for the colorimetric detection of oxytetracycline in rat serum. Issue 16 (23rd July 2021) - Zhang, Xinya; Qiao, Juan; Liu, Wei; Qi, Li
Abstract : LTN@AuNCs display peroxidase-like activity in a TMB-H2 O2 system. Their catalytic activity was enhanced by oxytetracycline. Using the mechanism, a protocol for highly selective and sensitive monitoring of rat serum drug was constructed. Abstract : Gold nanoclusters (AuNCs)-based nanozymes have been studied widely as they provide unrivaled advantages in terms of preferable enzyme-like activities, high stability, and good biocompatibility. Although the enzyme-like catalytic activity of AuNCs has been the object of extensive investigation, understanding how charges or reactive oxygen species on the surfaces of AuNCs can enhance their catalytic performance in the colorimetric sensing of drugs by regulating the catalytic activity of AuNCs is still a big challenge. Herein, l -tryptophanonitrile (LTN)-protected AuNCs (LTN@AuNCs) were prepared, and their nanozyme activity was investigated in the catalytic oxidation process of the peroxidase substrate, namely 3, 3′, 5, 5′-tetramethylbenzidine, in the prescence of hydrogen peroxide. Oxytetracycline induced the aggregation of LTN@AuNCs due to the electrostatic interaction between the positively charged LTN@AuNCs and the negatively charged drug. Importantly, the aggregated LTN@AuNCs produced more reactive oxygen species and significantly boosted their peroxidase-like activity. Subsequently, a colorimetric method for highly specific and sensitive detection of oxytetracycline was establised. The ultraviolet-visible absorbance at a wavelength of 650 nm of the aggregated-LTN@AuNCs exhibited a good linear relationship with oxytetracycline in a range of 0.5–15.0 μM ( R 2 = 0.994). The limit of detection was 0.3 μM. After oxytetracycline was abdominally injected in rats, the metabolic process of the drug in serums was further investigated by using the proposed sensing protocol. The improvable catalytic activity capability of the AuNCs-based nanozymes discloses its great potential in real bio-applications.